2006
DOI: 10.1007/s10749-006-0063-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-explosive splitting compounds and rational work parameters

Abstract: Non-explosive splitting compounds have come into use in construction, and also at certain dimension-stone quarries.Non-explosive splitting compositions (NSC) have come into certain use in construction, and also at some dimensionstone quarries. They are capable of splitting stone materials (concrete, reinforced-concrete, rocks) without the familiar negative factors inherent to the blasting method: scattering of fragments, effect of air-shock and seismic waves, liberation of poisonous gases, acoustic manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the water bath experiments, expansive pressure development was higher at the middle of the pipe (Figs. [8][9][10][11]. The pipe bottoms had slightly lower expansive pressure and hydration heat levels than those recorded at mid-height.…”
Section: Expansive Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…In the water bath experiments, expansive pressure development was higher at the middle of the pipe (Figs. [8][9][10][11]. The pipe bottoms had slightly lower expansive pressure and hydration heat levels than those recorded at mid-height.…”
Section: Expansive Pressurementioning
confidence: 99%
“…Experimental results presented herein generally showed that bigger diameter specimens resulted in larger expansive pressures (Figs. [8][9][10][11]. However, the expansive pressure development rate was not linear with borehole diameter.…”
Section: Expansive Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, tensile stress is generated around the hole. When it exceeds the ultimate tensile strength at the weakest point around the hole, the concrete cracks 12,28–30 . Therefore, the crushing degree of concrete depends on the relative size of the resistance of the concrete and the expansive pressure generated by the SCDAs.…”
Section: Introductionmentioning
confidence: 99%
“…They can be used under restricted conditions: in a dense urban setting, during reconstruction of active establishments, and when the entity being demolished is situated in a zone of operating mechanisms for which complete safety should be ensured. This applies, for example, to the reconstruction of concrete components in the bases of power-generating equipment [2].…”
mentioning
confidence: 99%